Procesamiento de imágenes usando Raspberry PI - Gordillo Gordillo, Verónica Raquel (2016)
This project develops a prototype for implementing a system capable of capturing images taken from a camera and processed on a platform Raspberry pi. The processing was carried out is the recognition and identification of faces, as well as the recognition of two facial gestures, to finally transmit images from one point to another, this whole process done in real time. The project uses devices such as Raspberry Pi, a camera and a computer for the operation of the processing system. To show in detail, as the objective of this project is demonstrated; the written document consists of four chapters, they are distributed as follows: Chapter 1: research topics in which the project is based are detailed; in particular, the study of analog and digital signals as detailed project basis. Chapter 2: Here the explanation of the design is done; and as implemented the system signal processing (images) from diagrams and research previously conducted. Chapter 3: This chapter tests system operation is performed, obtained once it has been implemented processing system.